Glencoe literature: the reader's choice, course 5 - Beverly Ann Chin et. al. (Unites States of America : McGraw Hill Education, 2000)
This book offer many opportunities to practice reading and writing skills that are tested on the Exit Level TAAS . More information on Texas writers and Texas literature. Texas connection and activities and a interactive literary map of Texas .
Unit1. The Short Story -- unit2. Nonfiction -- Unit3. Poetry -- Unit4. Drama -- Unit5. Legends -- Unit6. Humor .
Keywords: TEXAS LITERARY